2004
DOI: 10.1128/jb.186.13.4238-4245.2004
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Paths for Nonphysiological Transport of K + in Escherichia coli

Abstract: Mutants of Escherichia coli lacking all of the known saturable K+ transport systems, “triple mutants,” require elevated K+ concentrations for growth. K+ transport activity in such mutants, called TrkF activity, has low substrate specificity and a low rate that increases with increasing external pH. Attempts to isolate mutants requiring even higher concentrations of K+ failed, implying that either TrkF is essential or is composed of multiple minor K+ transport activities. Instead, we sought mutations that allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 33 publications
2
50
0
Order By: Relevance
“…To isolate mutant YbdG channels with altered gating frequencies, we randomly mutagenized the ybdG gene and screened for mutant channels that suppressed the potassium transport deficiency of a strain deleted for the major K + transport systems. This selection operates on the basis that the channel gates frequently enough to open the nonselective MS pore and allow K + ions to move into the cell down the membrane potential; through frequent cycles of transient openings, followed by rapid closure, the cell can acquire the K + needed for growth (31). Strain MJF622 is deficient for both potassium uptake and YbdG protein (Table S2) and requires ≥30 mM K + for rapid growth.…”
Section: Resultsmentioning
confidence: 99%
“…To isolate mutant YbdG channels with altered gating frequencies, we randomly mutagenized the ybdG gene and screened for mutant channels that suppressed the potassium transport deficiency of a strain deleted for the major K + transport systems. This selection operates on the basis that the channel gates frequently enough to open the nonselective MS pore and allow K + ions to move into the cell down the membrane potential; through frequent cycles of transient openings, followed by rapid closure, the cell can acquire the K + needed for growth (31). Strain MJF622 is deficient for both potassium uptake and YbdG protein (Table S2) and requires ≥30 mM K + for rapid growth.…”
Section: Resultsmentioning
confidence: 99%
“…alanine, concomitant with adaptations that retain the kink and its function in the protein (57). Interestingly, Buurman et al (58) suggested that multiple "aberrant" K + fluxes function as electrogenic uniport activities in E. coli and may together comprise an observed low affinity K + uptake capacity that has been termed TrkF. Perhaps some of these fluxes represent evolving transporters that are in the process of closing up small K + leaks created as membrane-embedded proline residues were replaced.…”
Section: Discussionmentioning
confidence: 99%
“…Such nonphysiological K þ uptake activity was reported for Prip and TrkG proteins of E. coli. 7) Of course, we cannot rule out the possibility that the observed K þ uptake partially contributes to the compensation for the growth defect of the E. coli TK2420 cells caused by concentrated Na þ . E. coli has a transport system for Na þ but not for mannitol.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli strain TK2420 (F À , thi, rha, lacZ, nagA, Á(kdpFAB)5, Á(trk-mscL 0 ) trkD1), 7) which is defective in the three major K þ transport genes, was the gift of Professor, Wolfgang Epstein of the University of Chicago. E. coli TO114 (ÁnhaA, ÁnhaB, ÁchaA), lacking the three Na þ /H þ antiport systems, NhaA, NhaB and ChaA, was the gift of Professor, Hiroshi Kobayashi of Chiba University, and was used in the detection of Na þ export activity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation